THE INFLUENCE OF THE NUMBER OF MEMBERS, TOTAL DEPOSITS AND TOTAL LOANS ON THE REST OF BUSINESS RESULTS IN PRIMER KOPERASI TRIBUANA II YEAR 2011-2020 - Muhammad Shidiq; Sri Laksmi Pardanawati; Yuwita Ariessa Pravasanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research aims to analyze the number of members, the number of deposits and the amount of loans to the remaining business results in Primer Koperasi Tribuana II. The type of research is quantitative research with secondary data. The population in this study is the Primary Annual Financial Report of the Tribuana Cooperative II with samples of reports on the number of members, the number of deposits, the amount of loans and the remaining amount of the Tribuana II Primary business results in 2011-2020. The method used in the sampling of this research is the total sample method. The method of data analysis in this study used the multiple linear regression analysis method using the SPSS test tool. The hypothesis testing method uses the F test, t test and the coefficient of determination (R2). Based on the results of the study, it can be concluded that the number of members, the number of savings and the number of loans together (simultaneously) affect the amount of remaining operating results in Primer Koperasi Tribuana II. The number of members and the number of loans have no significant effect on the amount of remaining operating results in Primer Koperasi Tribuana II. And the amount of savings has a significant effect on the amount of remaining operating results in Primer Koperasi Tribuana II. Keywords: Number of Members, Total Deposits, Total Loans, Total Remaining Operating Results.